Fundamental rights and best interests of the child in transnational families / edited by Elisabetta Bergamini, Chiara Ragni ; in collaboration with Francesco Deana. - Bergamini, Elisabetta; Ragni, Chiara; Deana, Francesco (Intersentia, 2019)
Families in Europe are increasingly shaped by the mobility of persons and multicultural backgrounds. This book is focusing on the protection of children in cross-border situations. What are the fundamental rights of children in transnational families, what is in their 'best interest', and how can their rights be safeguarded? There is much controversy on these rights and the accompanying uncertainty has resulted in considerable practical difficulties for those trying to implement them. In order to provide a clearer scope and insights into the nature of children's fundamental rights and their best interests, this book examines solutions provided by both EU and international law to the questions raised by the increasing incidence of transnational families as regards the protection of minors. It covers both substantive and conflict-of-laws rules. Differences in the substantive family laws of Member States still prevent an effective protection of the child or its family unit. This includes cases of migration, asylum, forced marriage, kafalah, but also rainbow families. Further, the role of human rights (mutual recognition of status and surrogacy agreements, adoption) and procedural rights (child abduction, Brussels II bis recast) in cross-border cases must be considered carefully. Fundamental Rights and the Best Interest of the Child in Transnational Families is a timely work on the implementation of the child's interests in the EU and covers the most relevant topics emerging from the rapid internationalisation of child and family law and from the increased mobility of families. Dr Elisabetta Bergamini is Associate Professor of International Law at the University of Udine, Italy. She teaches in and writes on international law, EU law and private international law, with particular emphasis on family law. From 2014 to 2016, she coordinated a Jean Monnet Module on European Family Law co-financed by the EU Commission. Dr Chiara Ragni is Associate Professor of International Law at the University of Milan, Italy, where she coordinated a Jean Monnet Module on European Family Law and Human Rights. Her main areas of expertise include private international family law, international criminal law and human rights law.